Psychopathological symptoms in Spanish subjects with gender dysphoria. A cross-sectional study. (3rd June 2021) - Castelo-Branco, Camil; RiberaTorres, Laura; Gómez-Gil, Esther; Uribe, Carme; Cañizares, Silvia
Abstract: Background: Most people with gender dysphoria have to face various stressful conditions, which make them more vulnerable to the development of psychopathological symptoms. Aims: The main goal was to compare psychopathological symptoms between individuals with gender dysphoria and those from the general population. Other secondary aims were to determine if there were differences between gender [male to females (MtFs) and female to males (FtMs)] and also according to cross-sex hormone therapy. Method: Symptom Checklist 90 Revised (SCL-90-R) questionnaire was administered to a sample of 205 subjects with gender dysphoria (MtFs = 129 and FtMs = 76). The control group included 530 individuals from the general population who took part in the Spanish validation of the SCL-90-R questionnaire. Results: Overall, individuals with gender dysphoria had higher scores on all SCL-90-R dimensions than the general population, except in the dimension of somatization, in which MtF and FtM subjects scored statistically higher than control males but not than control females. The mean scores of all dimensions except Depression (mean score of 1.17) were below 1, that is, between 0 (not at all) and 1 (occasionally). All dimensions did not differ when comparing MtFs and FtMs nor when comparing gender dysphoric subjects with or without cross-sex hormonal therapy. Conclusions: The results suggested that most subjects with gender dysphoria attending a gender unit reported higher levels of psychopathology than the general population. However, the scores were indicative of the lack of any clinically relevant psychopathological symptoms.